Genetic variation within the NR1H2 gene encoding liver X receptor β associates with insulin secretion in subjects at increased risk for type 2 diabetes - Ketterer, Caroline; Müssig, Karsten; Machicao, Fausto; Stefan, Norbert; Fritsche, Andreas; Häring, Hans-Ulrich; Staiger, Harald (Journal of molecular medicine (Berlin, Germany), 2011)
The liver X receptors (LXRs)-α and -β play a crucial role in control of insulin production and secretion in pancreatic β-cells. We hypothesized that common variants in the NR1H2 and NR1H3 genes, encoding LXR-β and -α, respectively, may alter pancreatic β-cell function. One thousand five hundred seventy-four subjects of European ancestry with elevated risk for type 2 diabetes were genotyped for the two NR1H2 single nucleotide polymorphisms (SNPs) rs2248949 and rs1405655 and for the four NR1H3 SNPs rs11039149, rs3758673, rs12221497 and rs2279238, and association studies with metabolic traits were performed. Metabolic characterization comprised an oral glucose tolerance test (OGTT) in all participants and, in addition, a hyperinsulinemic–euglycemic clamp and an intravenous glucose tolerance test (IVGTT) in subsets. One hundred per cent of common genetic variation (minor allele frequency ≥1%) within the NR1H2 and NR1H3 loci ( D ′ = 1.0; r ² ≥ 0.8) were covered by the six chosen tagging SNPs. NR1H2 rs2248949 was nominally associated with OGTT-derived first-phase insulin secretion and proinsulin conversion to insulin and significantly associated with the AUC of insulin levels during the IVGTT ( p = 0.007) after adjustment for age, gender, BMI and insulin sensitivity in the dominant model, with the minor allele conferring reduced pancreatic β-cell function to the carriers. In subjects of European ancestry at increased risk for type 2 diabetes, common variation within the NR1H2 gene impaired insulin secretion, which may facilitate the development of type 2 diabetes.